Murid-Murid Yesus Buta Huruf? Analisis Istilah Agrammatoi dan Idiotai dalam Kisah Para Rasul 4:13 - Sutoyo, Daniel; Tirakusuma, Rina Yugi; Retnowati, Eni (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. The writing of this article intended to answer the accusation that Jesus' disciples were illiterate and therefore could not have written his Gospel. The accusation is based on the statement in Acts 4:13 which refers to Peter and John as